The ways to improve the biological and morphological parameters of young fattening pigs - I. N. Mikolaychik; L. A. Morozova; A. V. Iltyakov; E. S. Stupina; O. P. Neverova; T. I. Uryumtseva (Теория и практика переработки мяса, 2022)
Studies were carried out to find the new ways to improve the efficiency of iodine use for the young pigs. During the scientific and economic experiment it was found that bringing iodine to the physiological norm, in combination with introduction of 3% bentonite clay into the diets of young fattening pigs, provided a positive effect on the morphological composition of carcasses, slaughter parameters and meat quality of the pigs. So fattening the yelts with the diets with a physiological norm of iodine in combination with 3% bentonite clay allowed young pigs of the 3rd experimental group to reach a slaughter weight of 78.95 kg at the age of 8 months, which is 10.1% more than in the control group, and 4.2% and 2.5% more in comparison with the 1st and 2nd experimental groups. The slaughter yield in yelts of the 3rd experimental group increased by 2.43% (P<0.05) compared to the control group. The largest (30.17 cm2) area of the “rib eye” was recorded in the 3rd experimental group, which is 5.60% more than the control one, while the carcasses of pigs of the 3rd experimental group contained muscle tissue by 4.74% (P<0.05) more than the same in the control group. Analysis of the Musculus longissimus showed a significant increase in protein content in the 3rd experimental group by 1.22% compared to the control group (P<0.05). The protein-quality parameter was significantly higher in the muscle tissue of young pigs of the 3rd experimental group and amounted to 10.90 (P<0.05), which is 1.12% higher than in the muscle tissue of the control group yelts. The maximum content of oleic acid was found in the lard of animals of the 3rd experimental group — 49.59, which is 1.28% (P<0.05) higher than in the control group.